(untitled) (Journal of Legal Studies, 2024)
The probation (trial) period employment contract and the internship are characterized by certain specificity in Georgian law. The issue of protecting the labor rights of probationary employees and interns, especially the termination of the contract, is even more specific. Moreover, the issue of political or other views, as one of the types of freedom of expression and the form of discrimination is interesting in the internship and trial period labor relationship. Based on the specificity of the Georgian case law, due to the simple termination of the probation period (trial period) employment contract, it is possible that the employer may abuse his right and thus violate the rights of the employee and/or intern. The following article mainly focuses on the research of these issues. The article also analyses the recent approaches of the Georgian courts’ practice and several cases of the International Court of Justice, which are the most well-known and often cited cases in foreign legal literature.